Lu-177-Dotatate plus long-acting octreotide versus high-dose long-acting octreotide in patients with midgut neuroendocrine tumours (NETTER-1): final overall survival and long-term safety results from an open-label, randomised, controlled, phase 3 trial - Strosberg, Jonathan R.; Caplin, Martyn E.; Kunz, Pamela L.; Ruszniewski, Philippe B.; Bodei, Lisa; Hendifar, Andrew; Mittra, Erik; Wolin, Edward M.; Yao, James C.; Pavel, Marianne Ellen; Grande, Enrique; Van Cutsem, Eric; et al. (Lancet Oncology, 2021)
Background The primary analysis of the phase 3 NETTER-1 trial showed significant improvement in progression-free survival with Lu-177-Dotatate plus long-acting octreotide versus high-dose long-acting octreotide alone in patients with advanced midgut neuroendocrine tumours. Here, we report the prespecified final analysis of overall survival and long-term safety results.
CRIS-Team WoS Importer:2021-12-31